Traveling Together: A Guide for Disciple-Forming Congregations - Jones, Jeffrey D. (Rowman & Littlefield Publishers, 2005)
Anyone concerned for the life and ministry of the church, who has a sense that things are not what they might be, and who is seeking a new understanding of congregational life and mission will find hope and help in the pages of this book. Jeff Jones takes his readers on a journey, providing a guidebook that maps out the factors facing congregations in this postmodern, post-Christendom world. With the heart of a pastor, Jones shows congregational leaders how to embrace the best parts of their church's rich heritage and reclaim it for a new day.